The Effect of Climate Change and Sustainable Agricultural Practices on Productivity and Food Security in Rural Areas in East Java - Judijanto, Loso; Machzumy, Machzumy; Rahayu, Silvia; Suryaningrum, Dyah Ayu (Westscience Press, 2023)
In rural East Java, Indonesia, this study examines the effects of climate change and sustainable farming practices on food security and agricultural output. A structural equation modeling approach was used to analyze the data from a survey of 250 farmers. The latent constructs' validity and reliability were validated by the measurement model evaluation, and each construct's uniqueness was guaranteed by discriminant validity analysis. Significant correlations were found by using the structural model: production was unexpectedly positively influenced by climate change, while food security was severely affected. Sustainable farming methods have a high positive correlation with production and food security. Demographic analysis shed light on the traits of the farmers in the sample. The evaluation of the model fit revealed that the relationships in the suggested model were satisfactorily represented. By providing useful insights for practitioners and policymakers pursuing sustainable agricultural development, this study advances knowledge of the complex dynamics of East Javan agriculture.